Gender differences in expatriate job performance - (:unkn) unknown (WILEY, 2003)
The purpose of this study was to examine gender differences in expatriate job performance. In doing so, we sought answers to two main questions: (1) Can women effectively perform expatriate job duties? (2) Can female expatriates be successful in a cultural environment that may be perceived to be unfriendly to females by Western standards? One hundred and ninety-three expatriates from 36 countries around the world, currently working in Turkey, constituted the sample. Job performance ratings were obtained from a host country national coworker of each expatriate. Men and women expatriates on average were rated quite similarly in terms of their job performance. Our study lends support to the employment of more gender diverse expatriates. The employment of more women. in the international workforce by multinational companies would enhance the quality of workforce diversity, and build more inclusive contexts in expatriate assignments, without decrements to job performance.
Keywords: WOMEN; MANAGERS